1986
DOI: 10.1007/bf02906889
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of carboxypeptidase I from malted barley

Abstract: Keywords: A m i n o acid sequence, sequence homology, serine carboxypeptidaseThe primary structure of malt carboxypeptidase I has been determined. The enzyme is composed of two peptide chains, an A-and a B-chain, linked by disulphide bridges. Fragments were obtained by chemical cleavages with either cyanogen bromide or hydroxylamine and by enzymatic cleavages with either trypsin, S. aureus V8 protease or proline specific endopeptidase (E.C. 3.4.21.26), sequenced and aligned to give the total sequence of the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…Earlier investigations (6) have shown that malt carboxypeptidase II, like wheat carboxypeptidase II (7) and malt carboxypeptidase I (5,18), is composed of two subunits where each subunit is constituted of two peptide chains, an A-chain and a B-chain, linked together by disulphide bridges. Determination of the amino acid sequence of serine carboxypeptidase II from barley malt revealed that the A-chain contained 260 amino acid residues ( Figure 9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier investigations (6) have shown that malt carboxypeptidase II, like wheat carboxypeptidase II (7) and malt carboxypeptidase I (5,18), is composed of two subunits where each subunit is constituted of two peptide chains, an A-chain and a B-chain, linked together by disulphide bridges. Determination of the amino acid sequence of serine carboxypeptidase II from barley malt revealed that the A-chain contained 260 amino acid residues ( Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…Chemical cleavage by cyanogen bromide and hydroxylamine and enzymatic digestion with trypsin of the reduced and alkylated chains was performed as previously described (18).…”
Section: Cleavage Of Peptide Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, CPD-Mlll is a monomeric enzyme, consisting of a single peptide chain while malt carboxypeptidases I and II are dimeric with each monomer consisting of two peptide chains, linked by disulfide bridges (2,6,23,24). Furthermore, CPD-M.~ contains far less carbohydrate than the other two carboxypeptidases.…”
Section: Discussionmentioning
confidence: 99%
“…The serine carboxypeptidases play an important role in this process and MmOLA ( 17,18,19) has presented evidence for the presence in malt of five such enzymes with complementary specificites. In this laboratory two of these have been isolated by affinity chromatography and their enzymatic properties and sequences have been determined (2,3,4,6,7,23,24). The isolation and characterization of CPD-Mm is reported here.…”
Section: Introductionmentioning
confidence: 99%